FORMALISASI HUKUM PIDANA ISLAM DALAM HUKUM PIDANA NASIONAL - Muwahid Muwahid (Al Hikmah: Jurnal Studi Keislaman, 2013)
This paper is a research library (library research) that will describe the formalization of Islamic criminal law in national criminal law.Formalization of Islamic criminal law in national criminal law can be done in two ways, namely the formalization of the principles of Islamic criminal law in national criminal law, and the formalization of norms of Islamic criminal law in national criminal law.Formalization Principles of Islamic criminal law in national criminal law did not experience any significant problems. Some principles of Islamic criminal law have become part of national criminal law. However, the formalization of the norms of Islamic criminal law in national criminal law experience obstacles and resistance, for example, efforts to formalize criminal offense stoning in adultery, hand amputation effort in the formalization of criminal offenses of theft and robbery, and efforts to formalize the death penalty in the murder offense.